Kelsen államelméletének alapjai - Tóthné Veszprémi, Bernadett (Debreceni Jogi Műhely, 2006)
Hans Kelsen was maybe the most famous philosopher of positivism. He became known from various theories that he made in the philosophy of law. Evolution was the characteristic feature of his scienfitic achievement. We can see this development for example in the theories ’origin of the state’ and ’will of the state’. In 1925 Kelsen made a resume of his theories. This was the "Allgemeine Staatsrechte", which was followed by the "Grundriss einer allgemeinen Theorie des Staates" (Basic rules of the theory of the state) in 1926, which was the shorter form of the previous resume. The following summary can be made of these studies: Kelsen made a thorough and detailed examination of the science of law, and realized that the point of view juristical a sociological theories are mostly influenced by the political tendencies. He criticized the dual system of the law of the rules and the law of the individual and he did not make difference between law and state. State is somehow the order of the human behaviour. State can be only mentioned as order, where human facts and human behaviour are in symphony. When the rules of the state are dominant, people observe its instructions, sometimes in spite of the different rules of nature. The will of the state doesn’t mean all the will of every human being of the state, it’s different, it means, that all the rules are made by the state are valid. State is not only some kind of authority and a valid order, which is followed by people of the state, it is also effective. This effective means, that people of the state observe the instructions of the state, they act according to these instructions. The system of the rules don’t make this effinence on its own, it is helped by the psychologically processes of human beings, that they are obedient to these rules. Law and state exist when its authority is felt, and this authority can be felt only in case, when law and state exist. Validity means, that rules must be followed. Validity doesn’t depend of efficiency (if it is regularly followed by people). Anyway, the rule which is followed by nobody is not valid, but there is no rule, which is followed by everybody. Permanency is not the prerequisite of validity. We can draw up the following question: why seems to be different the act of the state to other type of acts. Every act of the state is committed by a human being, nevertheless we consider this act to the state. Kelsen says, that ’state’ is a fixed point of special human acts. We can consider an act as natural or normative one. An act is natural, when it is caused by natural processes. But an act, when it is committed by a human, and the same time it is the manifestation of the state, it corresponds to the order of norms. Norms are rules, and if we follow them, our acts can be considered as a normative act. State can be considered as a group of acts, which can be obtained by force. Obtaining is not the way of enforcing the law, it has got only preventive and deterrent function. Kelsen sets up the formal an the material definition of the state itself, the definition of state organization, and makes difference of them. Formal state is a larger category, it means the order of law, and all the legal acts. Material state is a smaller category, it contains only some types of norms, like applying the law, and the rules of administration. Material state organization is also a smaller category than formal state organization. It means those acts which are used for obtaining, and also means the function of administration. In his studies Kelsen criticized the dual system of the law of the rules and the law of the individual and he said, that law and state is the same. State is equal to all the rules of law, and makes them valid. That is why state can be regarded as law.